A framework to enhance the design of reflective leadership development learing interventions - Harry-Nana, P.; Bosch, A. (South African Journal of Higher Education, 2020)
As workplaces grow more complex and multicultural, the need for a reflective leader has been identified as a key skill in the development of leaders. Business schools provide reflective leadership development learning interventions often with little empirical work to inform curriculum development. This study aimed to describe the perceived value of reflective learning in the leadership development of business students and how these insights could inform the design of leadership development interventions. Convenience sampling was employed through the use of social media. Primary data were collected via a questionnaire and follow-up interviews. The data showed that reflective learning did add value to participants during leadership development and that life story or autobiographical reflections were the most popular intervention types. The main findings emphasise the importance of taking prior reflective experiences, readiness and learning preferences of students into account when including reflective learning in leadership development interventions. These findings guided the development of a framework to enhance the design of reflective leadership development learning interventions. Such a framework can be used by higher education educators in the quest to cultivate the skill of reflection in leaders.